Triangular lipodermal flaps in Wise pattern reduction mammoplasty (superomedial pedicle): A novel technique to reduce T-junction necrosis. Issue 3 (August 2016) - Khalil, Haitham H; Malahias, Marco; Shetty, Geeta
Background: Although Wise pattern reduction mammoplasty is one of the most prevalent procedures providing satisfactory cutaneous reduction, it is at the expense of inevitable lengthier scars and wound complications, especially at the inverted T junction. Objective: To describe a novel technique providing tension-free closure at the T junction through performing triangular lipodermal flaps. The aim is to alleviate skin tension, thus reducing skin necrosis, dehiscence and excessive scarring at the T junction. Methods: One hundred seventy-three consecutive procedures were performed on 137 patients between 2009 and 2013. Data collected included demographics, perioperative morbidity and resected breast tissue weight. The follow-up period ranged from three to 30 months; early and late postoperative complications and patient satisfaction were recorded. Results: Superficial epidermolysis without T-junction dehiscence was experienced in eight (4.6%) procedures while five (2.9%) procedures developed full-thickness wound dehiscence. Ninety-four percent of patients were highly satisfied with the outcome. Conclusions: The technique is safe, versatile and easy to execute, providing a tension-free zone and acting as internal dermal sling, thus providing better wound healing with more favourable aesthetic outcome and maintaining breast projection.